Pengaruh Budaya Kesehatan dan Keselamatan Kerja (K3) terhadap Kinerja Karyawan PT. Angkasa Pura Logistik pada Masa Pandemi COVID-19 di Bandar Udara Internasional Yogyakarta, Kulon Progo - Hasni Maryam; Elisabeth Endang Prokosawati (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Due to the COVID-19 pandemic, PT. Angkasa Pura Logistik reduce employees until the remaining 75 employees. With the decrease in the number of employees, the workload per individual also increases. It can increase the risk to occupational safety and health. In addition, the threat of a new variant of COVID-19 makes the occupational health and safety (OHS) culture need to be considered. This research determines whether the occupational health and safety (OHS) culture affect the performance of PT. Angkasa Pura Logistik's employee during the COVID-19 pandemic at Yogyakarta International Airport. This study uses quantitative research methods, with employees of PT. Angkasa Pura Logistik at Yogyakarta International Airport as research subjects. The number of research samples was 63 people, determined by the Slovin formula. From the research that has been done, the following results are obtained: 1.) Occupational health and safety culture have a significant effect on the performance of employees of PT. Angkasa Pura Logistik during the COVID-19 pandemic at Yogyakarta International Airport. It is based on the value of t count (6.223) > t table (1.670), 2) The value of R Square of 38.8% obtained from the coefficient of determination test. So it is known that the occupational and safety culture (independent variable) has the influence of 38.8% on employee performance. A total of 61.2% were influenced by other variables outside of this research.